Investigating the Impact of NAAC Accreditation on Perceived Service Quality and Consumer Confidence for Higher Education in Madhya Pradesh, India - Verma, Sachin (Digital Repository of Theses - SSBM Geneva, 2025)
This research examines the influence of NAAC accreditation on service quality perception and consumer trust in higher education institutions (HEIs) in Madhya Pradesh, India. As the state is witnessing accelerated growth in higher education—along with regional imbalance in infrastructural facilities and access to them—NAAC accreditation has emerged as a vital quality determinant impacting institutional credibility as well as stakeholder choice. The research investigates six dimensions: awareness of accreditation, effect on service quality, effect on consumer confidence, comparison of accredited and non-accredited HEIs, challenges in gaining accreditation, and overall stakeholder perception towards higher education. A mixed methods research design was utilized, both with quantitative data through a well-structured questionnaire various students, parents, teaching staff, and administrators from accredited and non-accredited HEIs, and for a qualitative study, previous research was explored. SERVQUAL method was applied to quantify five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. It is revealed that NAAC accreditation information has a considerable impact on institutional choice by students and parents for accredited higher education institutions. Those organizations accredited performed more positively on service provision—providing superior infrastructure, faculty assistance, student services, and institution transparency regularly. NAAC status also bears consumer confidence that enhances trust, recruitment enhancement, and presumed career prospects. But the study also points to barriers in higher education systems, especially for non-accredited institutions. These constraints are mainly inadequate infrastructure, inadequate teaching staff, low levels of awareness concerning the accreditation processes, and poor administrative capacity. All these factors constrain first-time accreditation and continuous quality improvement. While the accreditation can trigger institutional growth and development, its impact is uneven due to such structural disadvantages. The study also discovers that NAAC accreditation is not merely an indicator of quality but also an indicator of institutional credibility and public accountability. But if it is to be harnessed as a tool for change, facilitatory policies such as earmarked grants, capacity building, and mentoring would have to bridge divisions in the sector. These findings are in consonance with the aspirations of the National Education Policy (NEP) 2020 and highlight the need for an inclusive, transparent, and context-sensitive accreditation process to improve higher education in Madhya Pradesh, India.